Determinants of poverty in Mozambique, 1996-97 - Datt, Gaurav; Simler, Kenneth R.; Mukherjee, Sanjukta; Dava, Gabriel (International Food Policy Research Institute, 2000)
This report presents an analysis of the structural determinants of living standards and poverty in Mozambique, which is based on nationally-representative data from the first national household living standards survey since the end of the civil war: Poverty in Mozambique is predominantly a rural phenomenon and is pervasive, with over two-thirds of the population falling below the poverty line. The degree of regional variation of poverty within the country is striking. The policy simulations that illustrate the impact that changes in the levels of determinants of poverty have on poverty levels allow us to identify six possible elements of a prospective poverty alleviation strategy for Mozambique. These include (1) increased investment in education, (2) sustained economic growth, (3) a sectoral pattern of growth favoring faster growth in the industrial and services sectors, (4) measures to raise agricultural productivity, (5) improved rural infrastructure, and (6) reducing fertility and dependency load within households. In conclusion, any meaningful poverty reduction strategy in Mozambique must give the highest priority to rural areas and must address these macro-level and household-level determinants of poverty in its policy formulations.